Foreign students' Customer Experience at the MIMG program from the University of Economics, Prague - Mejia Perdomo, David; Ryška, Tomáš, 1976-; Chavez, Jose Miguel Paz; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
The aim of this thesis is to look into the student experience provided to international students at the University of Economics and Business in Prague's Master in Management program as an insider researcher with an outsider perspective taking approach. To achieve this goal, this paper provides an empathetic view of personas developed based on ethnographic interviews conducted with individuals based on their stage on the program's customer journey map, as well as a detailed view of their experience as students. The outcome of this research suggests that the university's lack of a customer experience strategy has had a significant impact on MIMG's perceived level of quality. As a result, in order for the program to be a success in terms of customer experience, the university must develop a strategy that standardizes the quality of customer experience for all local and international students.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses